A COMPREHENSIVE REVIEW: EQUATIONS OF PIPE VIBRATION INDUCED BY INTERNAL FLUID FLOW - Ferdian, Yadi; Suwondo, Edy (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Some researchers have developed analytical models for the vibration of pipe conveying fluid internal flow with many forms of equation for different behavior of vibration, boundary conditions and assumptions. To predict the behavior of vibration with different boundary conditions and assumptions, it is needed to separate the equations into linear and nonlinear terms. This research will define the behavior of the linear terms and nonlinear terms, then classify the equations based on the two categories of terms. The general case of vibration of pipe has been chosen based on industry applications. In general, for each of the cases the vibration of pipe conveying fluid has nonlinear terms due to some forces acting on the pipe, except flexural force, centrifugal force, Coriolis force and inertia force in the fluid and pipe.